Probability Management for Water Finance and Resource Managers. Issue 1 (19th January 2021) - Chesnutt, Thomas W.; Hollis, Michael; Mitchell, David L.; Kavanagh, Shayne; Pekelney, David M.; Putt, Brian; Savage, Sam
Key Takeaways: From determining future water demands to setting rates, it's a given that most planning related to water requires managers to deal with uncertainties. If uncertainties are understood more clearly, then stakeholders buy in to resulting decisions more readily. Probability management provides principles, methods, standards, and tools to reduce the cost of confronting uncertainty when making decisions.